Meningkatkan Kesadaran tentang Penyandang Autisme untuk Dewasa Muda melalui Animasi Eksperimental: Meningkatkan Kesadaran tentang Penyandang Autisme untuk Dewasa Muda melalui Animasi Eksperimental - Luna, Sabine; Grahita, Banung (Wimba : Jurnal Komunikasi Visual, 2024)
Many with Autism Spectrum Disorder (ASD) struggle to achieve independence due to a lack of understanding and acceptance, particularly among young adults. To bridge this gap, this project proposes an experimental animation designed to foster empathy. Through a combination of literature review, interviews with psychologists and ASD companions, and participatory observations at an autism center, the project will gain insights into the lived experiences of ASD and the challenges young adults pose to social inclusion. The animation itself will leverage the flexibility of experimental animation to portray the frustrations and difficulties encountered by people with ASD due to social exclusion. Ultimately, the project aims to create a bridge of understanding through emotional connection, fostering empathy and acceptance among young adults towards individuals on the autism spectrum.